The declining significance of triad societies in transnational illegal activities. A structural deficiency perspective - Zhang, Sheldon (The British journal of criminology, 2003)
Through field observations and interviews with Chinese human smugglers and heroin traffickers in the past few years, we have come to realize that a generation of non-triad organized criminals has emerged as an active, if not dominant, force in illegal transnational enterprises. The rapid expansion of global commerce, coupled with shrinking totalitarian societies, has created many opportunities for people of all stripes to come into the illicit market place. While the American law enforcement policies and strategies are still influenced by the dated La Cosa Nostra model, this new generation of Chinese organized criminals enjoying unprecedented opportunities in their provision of illicit services and goods. Empirical studies thus far have not been able to link these transnational organized crime groups to any traditional triad societies. We present a conceptual framework here to argue that triad's entrenched culture and patterns of organization, which have served them well for centuries, are incompatible with conditions necessary for entering into present-day transnational criminal activities